Decolorization of Biogas Effluent from Palm Oil Mill Using Combined Biological and Physical Methods - Bunrung, Surasak; Prasertsan, Suteera; Prasertsan, Poonsuk (Agriculture and Natural Resources, 2014)
Two mixed cultures (Super LDD.1 and Super LDD.2) were used as inocula (10%) for the decolorization and treatment of biogas effluent from palm oil mill (BEPOM) under aerobic (2.5 volume of air per volume of medium per minute, vvm) and microaerobic conditions, respectively. With the supplementation of 10% palm oil mill effluent (POME) as nutrients, Super LDD.1 and Super LDD.2 showed higher decolorization than the Super EM culture under microaerobic conditions after 4 d cultivation. The optimum inoculum size for both sources was 20% (volume per volume) and Super LDD.1 produced higher decolorization (27.0%) and phenol removal (20.4%) than Super LDD.2 (16.7% and 12.1%, respectively) after 2 d cultivation. However, Super LDD.1 exhibited slightly lower chemical oxygen demand (COD) removal than Super LDD.2 (27.8% and 29.2%, respectively) after 6 d cultivation. The effluent after treatment by Super LDD.1 was subsequently tested for the effect of pH and palm ash concentration (1–15%, weight per volume) under mixing conditions (on 125 rpm shaker) at room temperature (30 ± 3 °C) for 1 h. The highest decolorization (84.7%), phenol removal (90.8%) and COD removal (88.9%) were achieved at 15% (w/v) palm ash. The results indicated the potential treatment of BEPOM using a biological method (Super LDD.1 culture) in combination with a physical method (palm ash) which was better than using each treatment alone.